Structure and Composition of Mangrove Vegetation on Kelasa Island: Dominance of Rhizophora apiculata and Its Implications for Coastal Ecosystem Sustainability - Akhrianti Irma; Oka Arizona Mohammad; Harapan Putera Batubara Geothani (BIO Web of Conferences)
Mangroves provide essential ecosystem services such as capturing carbon, habitat provision, and shoreline protection, making them essential for coastal sustainability.Understanding their structure and composition is essential for fostering conservation efforts and ensuring long-term resilience. This study investigates the mangrove vegetation on Kelasa Island, revealing key ecological trends relevant for future management. Using transect line and plot sampling across nine 0.09 ha plots, 117 mangrove individuals were identified, predominantly Rhizophora apiculata and Rhizophora mucronata. Density varied by growth stage, with mature trees averaging 87 individuals/ha, saplings 17 individuals/ha, and seedlings 13 individuals/ha. Despite lower species diversity compared to nearby islands in the Bangka Belitung Province, Kelasa Island exhibits higher seedling density. The mangrove community is largely dominated by R. apiculata, indicating a trend towards monospecific dominance with robust regeneration. The forest spans approximately 2.57 ha on the island’s eastern coastline, characterized by sandy coral fronts and muddy-rocky substrates. Though relatively young and sparsely distributed, the mangrove stands show ecological stability, demonstrated by high dominance indices and uniformity across growth stages. These findings underscore the critical role of R. apiculata in maintaining ecological balance within the Kelasa Island mangrove ecosystem under moderate environmental pressures. The study highlights the importance of conserving these mangrove communities for their resilience, coastal protection, and biodiversity contributions.